Freshwater fishes in traditional markets of the largest urban city of Caraga Region, Philippines - Libot, Antonette B. (Philippine Journal of Science, 2024)
Butuan City, a hub surrounded by freshwater bodies, is the commercial center of the Caraga Region, Philippines. This paper analyzes freshwater fish inventory and market trends, focusing on major commercial and “talipapa” networks in the region's largest urban city. Twelve (12) markets were surveyed, including three major public and nine local artisanal stalls locally known as “talipapa.” The study identified 15 freshwater fish species across 12 families, with Apogonidae, Chanidae, and Gobiidae showing the highest species diversity, each with three species. Major markets exhibited greater species variety compared to “talipapa.” Only 15.38% of species were found in all markets, whereas 61.53% were exclusive to specific markets. Two species were noted as “endangered” or “vulnerable,” whereas others were categorized as “least concern,” “data deficient,” or “not evaluated.” Most species (66.66%) were native, with the remainder introduced. Most fish sold were wild-caught, with only four species sourced from local farms. Prices varied based on market location, size, quality, and availability. Certain species were considered rare, appearing in markets for only 10–30% of the year, with consistently moderate to high demand. The study documented the illegal capture and sale of “luyab” or “saguyon” (juvenile Glossogobius giuris) in major public markets and “talipapa,” which violates the Philippine Fisheries Code of 1998 and the unified local ordinance on sustainable fisheries for Lake Mainit communities. The study recommends conducting long-term assessments of market trade dynamics for freshwater fishes, especially of lesser-known species, to update records and verify the diversity of small-scale inland fisheries in landing sites and wet markets. Policymakers should consider strategies to sustain traditional market stalls amid evolving market conditions.